Pelatihan AutoCAD untuk Meningkatkan Kompetensi Gambar Teknik Siswa Kelas XI SMK Negeri 2 Binjai: Pelatihan AutoCAD untuk Meningkatkan Kompetensi Gambar Teknik Siswa Kelas XI SMK Negeri 2 Binjai - Anggiat Daniel Anderson Munthe; I Wayan Putra Jayantara; Fikryah Atikah Pane; Ivana Christine Sembiring; Aula Sekar Arum Pertiwi; Melvi Maulita Napitupulu; Titonik Feberman Hia (Universitas Mataram, 2026)
This community service activity aims to improve the competence of vocational high school students in using AutoCAD software for technical drawing. The activity was conducted at SMK Negeri 2 Binjai involving 32 students of grade XI. The method used in this activity was a hands-on training approach combined with pre-test and post-test evaluation to measure the improvement of students’ competencies. The training materials included initial AutoCAD settings, layer management, dynamic block usage, title block creation, and proper layout and printing scale settings. The results showed that students competencies increased significantly after the training. The average pre-test score was 75.63 with a median of 75 and a score range of 35–100. After the training, the average post-test score increased to 90.94 with a median of 95 and a range of 60–100. The results indicate that practical-based AutoCAD training effectively improves students’ skills in producing structured and standardized technical drawings. This activity also helps students understand professional workflows commonly applied in the construction industry. Therefore, AutoCAD training can be considered an effective strategy to enhance vocational students' technical drawing competencies.